Pengaruh Metode Bercerita terhadap Perkembangan Berbicara Anak Usia 5-6 Tahun - Tesya Cahyani Kusuma; Riwayati Zein; Nadila Sari (Jurusan Pendidikan Islam Anak Usia Dini, 2021)
This research is motivated by the dominant use of conventional methods in learning. This results in children being unable to speak fluently with complex sentences and divorce events coherently. This study aims to determine the effect of storytelling methods on the development of speaking children aged 5-6 years. This type of research is an experimental nonequivalent group pretest-postest designed. The population in this study were all class B students at the State II Kindergarten in Padang City. The sampling technique used purposive sampling technique, so that class B1 was obtained as the experimental group and B3 class as the control group. Data collection techniques in this study used observation, interviews, and documentation. this study uses the formula t-test which is preceded by an analysis prerequisite test using the normality test and homogeneity test. Based on data analysis, the average test results of the experimental class were 85.88 and the control average was 76.18. This research was proven from the results of the t-test with a significant level of 0.04 <0.05, the H1 hypothesis was accepted. The results showed that there was a significant influence on the use of the Storytelling Method on the Development of Speaking Children aged 5-6 Years at TK Negeri II Padang.